1992
DOI: 10.1007/bf00166698
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the mating plug in Atrophaneura alcinous (Lepidoptera : Papilionidae)

Abstract: At mating, males of Atrophaneura alcinous plug the female copulatory duct with a secretory material, but some females copulate several times and can receive spermatophores from different males up to three times. Remating by plugged females mostly takes place shortly after the first mating, when the freshly formed first plug has not completely hardened. A freshly formed plug can be pressed aside or tunneled by the male aedeagus, and thus intromission and subsequent spermatophore transfer are sometimes possible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 12 publications
0
29
0
1
Order By: Relevance
“…In some insect taxa, a lifetime copulation number can be easily estimated by counting number of spermatophores remaining in the spermatheca (e.g. Matsumoto & Suzuki 1992), but more clarification is needed on the actual conditions for multiple mating in a wild population. In coccinellid ladybird beetles, mating behavior was observed in laboratory conditions by Obata (1987Obata ( , 1988.…”
mentioning
confidence: 99%
“…In some insect taxa, a lifetime copulation number can be easily estimated by counting number of spermatophores remaining in the spermatheca (e.g. Matsumoto & Suzuki 1992), but more clarification is needed on the actual conditions for multiple mating in a wild population. In coccinellid ladybird beetles, mating behavior was observed in laboratory conditions by Obata (1987Obata ( , 1988.…”
mentioning
confidence: 99%
“…Alternatively, the males that survive towards end of adult flight may have depleted their body resources, producing incompletely developed sphragis during belated mating (Pierre 1985;Matsumoto & Suzuki 1992;M.S. Fred, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The mating plug, another product of the AGs, was found earlier to prevent additional inseminations in bumblebees (Baer et al, 2001;Duvoisin et al, 1999) and non-social insects (Bretman et al, 2010;Dottorini et al, 2012;Matsumoto and Suzuki, 1992;Polak et al, 2001), and was suggested to prevent multiple insemination in fire ants (Mikheyev, 2003). However, mating plugs are unlikely to have a similar function in A. colombica.…”
Section: Mating Plugs and Their Putative Functionsmentioning
confidence: 99%